2019
DOI: 10.1001/jamanetworkopen.2019.5463
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Brief Admission to Hospital by Self-referral for Individuals Who Self-harm and Are at Risk of Suicide

Abstract: Key Points Question Is self-referred brief admission more effective than treatment as usual in reducing the use of inpatient services for individuals who self-harm and are at risk of suicide? Findings In this randomized clinical trial of 125 adults in Sweden, the brief admission group did not show reduced inpatient service use compared with the control group. Both groups showed significant decreases in days admitted to the hospital and in emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 31 publications
(37 reference statements)
2
58
1
Order By: Relevance
“…One hundred twenty-five participants with current episodes of self-harm and/or recurrent suicidal behavior, as well as at least three diagnostic criteria for borderline personality disorder (BPD), were recruited from four psychiatric inpatient clinics in Skåne, Sweden, for a project evaluating the effects of Brief Admission to the hospital by self-referral (37). All participants were undergoing treatment at a psychiatric outpatient clinic throughout the study.…”
Section: Methods Participantsmentioning
confidence: 99%
“…One hundred twenty-five participants with current episodes of self-harm and/or recurrent suicidal behavior, as well as at least three diagnostic criteria for borderline personality disorder (BPD), were recruited from four psychiatric inpatient clinics in Skåne, Sweden, for a project evaluating the effects of Brief Admission to the hospital by self-referral (37). All participants were undergoing treatment at a psychiatric outpatient clinic throughout the study.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Self‐admission has been offered in Norway and the Netherlands for over a decade as a tool in the treatment of longstanding mental illness such as schizophrenia, bipolar disorder, and borderline personality disorder (Strand & von Hausswolff‐Juhlin, 2015). Similar programs have been introduced in Sweden (Eckerström et al, 2019; Strand, Gustafsson, Bulik, & von Hausswolff‐Juhlin, 2015; Westling et al, 2019) and Denmark (Thomsen et al, 2018). The self‐admission model has previously been described in detail in this journal (Strand et al, 2015; Strand, Bulik, von Hausswolff‐Juhlin, & Gustafsson, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…The goal of such a method is to increase the autonomy of patients with severe psychiatric profiles by promoting early help‐seeking behaviour and thereby reducing the more traditional coercive interventions, which in turn, reduces the total time spent in inpatient care. The first randomized clinical trial regarding BA for patients with BDP studied effects after 12 months (Westling et al, 2019). The trial showed a reduction in days with compulsory admission and non‐suicidal self‐injuries, and also greater improvements in the mobility domain of daily life functioning compared to the control group (Westling et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first randomized clinical trial regarding BA for patients with BDP studied effects after 12 months (Westling et al, 2019). The trial showed a reduction in days with compulsory admission and non‐suicidal self‐injuries, and also greater improvements in the mobility domain of daily life functioning compared to the control group (Westling et al, 2019).…”
Section: Introductionmentioning
confidence: 99%